-6(8k+1)+3=

Simple and best practice solution for -6(8k+1)+3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(8k+1)+3= equation:


Simplifying
-6(8k + 1) + 3 = 0

Reorder the terms:
-6(1 + 8k) + 3 = 0
(1 * -6 + 8k * -6) + 3 = 0
(-6 + -48k) + 3 = 0

Reorder the terms:
-6 + 3 + -48k = 0

Combine like terms: -6 + 3 = -3
-3 + -48k = 0

Solving
-3 + -48k = 0

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + -48k = 0 + 3

Combine like terms: -3 + 3 = 0
0 + -48k = 0 + 3
-48k = 0 + 3

Combine like terms: 0 + 3 = 3
-48k = 3

Divide each side by '-48'.
k = -0.0625

Simplifying
k = -0.0625

See similar equations:

| 7x+1.5=-4+11.4 | | -2w+46=7(w+4) | | 144=6(1-4v)-6v | | 2(7-a)=14 | | x/2=-17 | | (.5x-73)=90 | | 5(6x+7)=28-(5x+7) | | 22+x=22-x | | -3(w-5)=-7w+31 | | -4+7(-7-5n)= | | -4u-3=9(u+4) | | -8(4+n)-8= | | 11x=222 | | 0.22y+0.03(y+4000)=2370 | | 3c+9c= | | q-9=-19 | | 4v-15=49 | | -9(v-4)=5v+4 | | .4x-73=90 | | -8(4+n)= | | 9-9=-19 | | 5+-(11)-(-11)= | | 15u+5v-3u+17v= | | -19+p=-9 | | 7(2x-10)-3=7(x-5)+4 | | -19+p=9 | | 8=16.9-a | | cosine(x)=-0.25 | | 8x-4(1+X)= | | 10=.11(0)+b | | X*x+1=101 | | 6/5÷6/ |

Equations solver categories